Identical Strain of Mycobacterium conceptionense Isolated from Patients at 2 Veterans Affairs Medical Centers within the Same Metropolitan Area over a 4 Year Period. (4th October 2017) - Oda, Gina; Winters, Mark; Pacheco, Susan M; Sikka, Monica; Bleasdale, Susan; Dunn, Bruce; Winters, Benjamin; McDuffee, Etta; Bumsted, Amelia; Holodniy, Mark
Abstract: Background: Hospital epidemiologists at 2 Veterans Affairs Medical Centers (VAMCs A and B) within the same metropolitan area were alerted in 2015 by a shared VA reference laboratory to a possible cluster of Mycobacterium fortuitum complex (MFC) isolates, including M. farcinogenes/senegalense, from patients at both facilities. Methods: Clinical samples were cultured for mycobacteria using standard methods and isolates were initially identified using AccuProbe (Hologic) or MALDI-TOF (Bruker). Stored MFC isolates from 2012-2015 were then analyzed using hsp and rpoB gene population sequencing, and compared with reference MFC sequences to determine species and genetic relatedness. One-liter water samples from sinks and ice machines on critical care units of both hospitals were cultured for nontuberculous mycobacteria using CDC published methods. Cohort clinical data were abstracted from electronic health records. Results: We determined that 31 of 38 MFC isolates (19 VAMC A, 12 VAMC B) were an identical strain of M. conceptionense by rpoB sequencing. The same strain was found in a critical care unit ice machine at VAMC A. No other water samples from either facility contained this species. Ten additional MFC isolates from other VAMCs were also sequenced and none were M. conceptionense . Isolates came from critical care patients (27/31, 87%), inpatient non-critical care units (3, VAMC A) and 1 outpatient (VAMC B Pulmonary Clinic). Infection occurred in 2 patients (6%): bacteremia and mediastinitis 15 days after cardiac surgery (VAMC A), and pneumonia in an immunocompromised patient (VAMC B). Both patients received targeted antimicrobial therapy and recovered. The remaining 29 isolates were of respiratory origin and determined not to be clinically significant. Conclusion: M. conceptionense was isolated from multiple patients over 4 years at 2 VAMCs in the same metropolitan area. Conventional methods (AccuProbe, MALDI-TOF) and hsp did not adequately differentiate MFC species; only rpoB sequencing identified M. conceptionense . An ice machine may have been one source at VAMC A; no source was determined for VAMC B. M. conceptionense is an unusual pathogen, causing infection in only 2 cases in our cluster. Disclosures: All authors: No reported disclosures.